Dinâmica linear e aplicações - Cruz, Erijhonson de Braga (Brasil, 2025)
The main objective of this work’s is to study the geometry of the trajectories whose dynamic have linear behavior and give some applications. The research was approached to encourage the study of dynamical systems by a simple approach and using tools from the theory of linear operators. The Mathematical modeling of systems whose dynamics are linear can be analyzed initially with a simple approach through the theory of matrix and linear operators, which allows students to study and learning on a dynamical systems that present non-linearities, and thus deal with the modeling of a process in situations of different contexts. In this direction of study, the research work has been carried out focusing on linear dynamics and some applications.